Latitudinal variation in suppression of flower bud formation at high temperature in four native dandelions (Taraxacum spp.) with different distributions and genetic structures in Japan. Issue 1 (5th April 2016) - Yoshie, Fumio
Abstract : The control of the response of flowering to temperature plays a key role in successful range‐expansion of plants. A previous study showed that the suppression of flower‐bud formation at high temperature in Taraxacum officinale decreases genetically with latitude from north to south in Japan. The present study investigated whether similar trait variation occurs among populations of native Taraxacum species in Japan. Seedlings of T. albidum (a low‐ and mid‐latitude allopolyploid), T. japonicum (a mid‐latitude diploid) and T. venustum (a high‐latitude autopolyploid) were grown at three temperatures. Time to flower‐bud appearance increased with temperature in T. japonicum and T. venustum, but did not increase in T. albidum . Time to flower‐bud appearance did not differ significantly among the three species at 14°C, but it was shorter in T. albidum than in the other two species at 19°C and 24°C. The early appearance of buds of T. albidum was confirmed by another experiment in which plants of 18 populations from the three species and T. platycarpum (a mid‐latitude diploid) grown at 19°C were used. The results clearly indicate that high‐temperature suppression of flower‐bud formation was lower in low‐latitude species than in high‐latitude species. This interspecific variation is analogous to the intraspecific variation in T. officinale . Time to bud appearance of five populations in T. albidum was homogeneous within and between the populations. The results suggest that the five populations are monoclonal and lack the sensitivity of suppression of flower‐bud formation to high temperature. Abstract : This study showed that high‐temperature suppression of flower bud formation is lower in low‐latitude species than that in high‐latitude species. This interspecific variation associated with latitude is analogous to the intraspecific variation found among Taraxacum officinale populations in the previous study. The similar latitudinal variation within and between species supports the adaptive explanation that dandelions in low latitudes avoid an increase in the dormant flowering period with increasing temperature by raising their upper threshold temperature for flower bud formation. This study suggests that one hybrid lineage of T. albidum dominant throughout the distribution range disappears the high‐temperature suppression of flower bud formation.